2015
DOI: 10.1245/s10434-015-4695-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of Adherens Junctions Associated Protein 1 Predicts Recurrence of Hepatocellular Carcinoma After Curative Hepatectomy

Abstract: AJAP1 may function as a key regulatory molecule associated with the recurrence of HCC. Hypermethylation of the AJAP1 promoter is a key regulatory mechanism controlling AJAP1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 52 publications
4
21
0
Order By: Relevance
“…6 One study found that low AJAP1 mRNA levels in HCC tissues were associated with poor outcome after curative hepatectomy, particularly for disease-free survival (DFS). 14 In the present study, we showed that AJAP1 was highly expressed normal liver tissue, and was downregulated with HCC progression. In vitro experiments also indicated that AJAP1 expression was negatively correlated with metastasis.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…6 One study found that low AJAP1 mRNA levels in HCC tissues were associated with poor outcome after curative hepatectomy, particularly for disease-free survival (DFS). 14 In the present study, we showed that AJAP1 was highly expressed normal liver tissue, and was downregulated with HCC progression. In vitro experiments also indicated that AJAP1 expression was negatively correlated with metastasis.…”
Section: Discussionsupporting
confidence: 54%
“…It was recently reported that the AJAP1 promoter is highly methylated in HCC cell lines and tissues, suggesting that decreased levels of AJAP1 mRNA are linked to HCC recurrence. 14 …”
mentioning
confidence: 99%
“…HLE, HLF, HuH1 and HuH7 were obtained from the Japanese Collection of Research Bioresources Cell Bank (Osaka, Japan) (16). HuH2 cells were a gift from Aichi Cancer Center (Nagoya, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…According to these analyses, shrew-1 (also called AJAP1) is a tumor suppressor whose gene becomes hypermethylated and thus epigenetically silenced in the course of tumor development (Chen et al, 2014; Cogdell et al, 2011; Ezaka et al, 2015; Lai et al, 2014). In some cases described for glioblastoma, loss of function of shrew-1 occurs through deletions of the respective genomic region chr1p36 harboring its gene (Ernst et al, 2009; Lin et al, 2012; McDonald et al, 2006; Milde et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The function of shrew-1 in epithelial tissues remains elusive, however, it is known from progressive promoter silencing or gene deletion in brain tumors that shrew-1 can act as a tumor suppressor protein (Cogdell et al, 2011; Ernst et al, 2009; McDonald et al, 2006; Milde et al, 2009). More recent evidence indicates that the SHREW-1/AJAP1 gene is also silenced in other tumor types such as gastric (Matsusaka et al, 2011), cervical (Chen et al, 2014) and endometrial cancer (Lai et al, 2014), or hepatocellular carcinoma (Ezaka et al, 2015). …”
Section: Introductionmentioning
confidence: 99%